Antibiogram study and antibiotic use evaluation using gyssen method in patients with diabetic foot - Fadlilah, Umul; Hasmono, Didik; Wibisono, Yudi Agung; Melinda, Mia (Folia Medica Indonesiana, 2017)
Foot infection is a common and serious problem in people with diabetes, which require proper management (diagnostic and therapeutic approaches) that can be cured. Empiric antibiotic regimen should be based on clinical data and bacteria pattern that are available, but definitive therapy should be based on the results of the infected tissue culture. The selection of initial antibiotic therapy was difficult and unwise use can lead to antibiotic-resistant. Evaluation is needed for using antibiotics to benefit wisely. The aim of this research is to analyzed the pattern of bacteria in diabetic foot and to its sensitivity test to antibiotics, analyze empiric antibiotics that can be recommended, and analyzed the use of antibiotics by Gyssen method. Data was analyzed with observational studies (descriptive non-experimental), retrospectively and prospectively in patients diabetic foot infection that met inclusion criteria. Retrospective data are used to analyzed bacteria pattern and its sensitivity test, while prospective data are used to evaluated the use of antibiotics based on bacteria pattern, during the period of late March-early August 2015 at Mardi Waluyo Hospital. Evaluation was conducted by Gyssen method. The results, retrospective data samples obtained 30 infection bacteria during August 2014-March 2015. The prevalence of gram-negative bacteria as 53.33% with most types of bacteria E.coli and Klebsiella oxytoca (13.33%), and gram-positive bacteria as 46.67% with the highest bacteria are Staphylococcus spp. and Streptococcus spp. From the prospective data in inclusion criteria, 13 patients with the highest prevalence of gram-negative bacteria are Klebsiella oxytoca (28.57%), and most gram-positive Staphylococcus auerus (35.71%). While the qualitative analysis of antibiotic use was conducted on 50 types of antibiotics. The results of the qualitative analysis using Gyssens method obtained category as 62%, 2%, 14%, 2B category as 26%, 3A category as 10%, 4A category 52%, 4B category as 6%, 4C category as 8% and there are no use of antibiotics in the category V and VI. Conclusions, Gyessen method can show that the use of antibiotics in diabetic foot patients in Mardi Waluyo hospital is dominated by inaccuracy in choice of antibiotic, and inaccuracies in the interval antibiotics.